2020
DOI: 10.3390/ijms21207612
|View full text |Cite
|
Sign up to set email alerts
|

Light Energy Dose and Photosensitizer Concentration Are Determinants of Effective Photo-Killing against Caries-Related Biofilms

Abstract: Caries-related biofilms and associated complications are significant threats in dentistry, especially when biofilms grow over dental restorations. The inhibition of cariogenic biofilm associated with the onset of carious lesions is crucial for preventing disease recurrence after treatment. This in vitro study defined optimized parameters for using a photosensitizer, toluidine blue O (TBO), activated via a red light-emitting diode (LED)-based wireless device to control the growth of cariogenic biofilms. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
0
17
1
1
Order By: Relevance
“…Encapsulating the TBO inside the microemulsion was also associated with improved TBO’s biocompatibility. Our previous report showed that 100 μg/mL TBO did not induce significant toxicity against mouse monocyte-macrophage cells . However, the results of this study illustrated that TBO alone was very toxic against the human gingival fibroblasts, as the percentage of fibroblast viability was 33.4%.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…Encapsulating the TBO inside the microemulsion was also associated with improved TBO’s biocompatibility. Our previous report showed that 100 μg/mL TBO did not induce significant toxicity against mouse monocyte-macrophage cells . However, the results of this study illustrated that TBO alone was very toxic against the human gingival fibroblasts, as the percentage of fibroblast viability was 33.4%.…”
Section: Resultscontrasting
confidence: 56%
“…When the TBO was incorporated inside the microemulsion, the viability increased by 1-fold, resulting in more enhanced viability. Such results may encourage higher concentrations of TBO within the microemulsions to maximize the antibacterial reduction, as increasing the concentration of TBO is associated with an enhanced antibiofilm effect . Unlike most of the nanoparticles, increasing the SPIONs concentration was associated with improved biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process causes environmental changes that result in hydroxyl radicals, which are one of ROS's reactive forms [35]. Following the activation of the device by light,PS, the targeted cells are killed by a succession of released oxygen ions and free radicals [36,37]. One of the significant benefits of aPDT is its reliance on enhanced penetration and accessibility of oxygen species [38,39] Type II: Light activates the PS, which then reacts on molecular oxygen with in ground state so create excited state oxygen.…”
Section: Antimicrobial Photodynamic Therapy (Apdt)mentioning
confidence: 99%